Tehlikeli Madde Taşımacılığı Güzergâh Seçimi Problemi İçin Stokastik Bir Risk Analizi - Erdal, Hamit (Muş Alparslan Üniversitesi, 2018)
Tehlikeli maddetaşımacılığı günümüzde can ve mal güvenliğinin sağlanması ve faaliyetlerinaksamadan yürütülebilmesi için üzerinde önemle durulması gereken konulardanbiridir. Artan sanayileşme düzeyi ile birlikte daha fazla kullanılmaya başlanantehlikeli maddelerin bir noktadan diğer bir noktaya güvenle taşınması dahaönemli bir hâl almıştır. Tehlikeli maddelerin taşınmasında her ne kadar tümtaşıma modları etkin olarak kullanılsa da en çok karayolu kullanılmaktadır. Buyüzden, tehlikeli maddelerin içerdiği risk göz önüne alınarak, daha titiz birtaşıma ve dolayısıyla daha etkin bir risk yönetimi gerekmektedir. Bu çalışmadatehlikeli madde taşımacılığının maliyet etkin, güvenli ve kesintiye uğramadangerçekleştirilebilmesi için en uygun güzergâhın belirlenmesi amaçlanmıştır. Buçerçevede Gaziantep ile Erzurum illeri arasında tehlikeli madde taşımacılığı yapanbir firmanın yetkilileriyle yüz yüze görüşmeler gerçekleştirilerek SMAA-2yöntemiyle tehlikeli madde taşımacılığı güzergâh seçimi yapılmıştır.

Today, hazardousmaterials’ transportation is one of the important issues that must be takeninto consideration in order to ensure the safety of life and property and tocarry out operations without any interruption. With the increasing level ofindustrialization, it has become more important to move hazardous materials, which have begun to be used more frequently, safely from one point to another.Although all transportation modes are used effectively in the hazardousmaterials’ transportation, mostly the roads are used.  For this reason, by taking into considerationthe risk, involved in hazardous materials, they require more rigoroustransportation and more effective risk management. In this study, it is aimedto determine the most appropriate route for the hazardous materials’transportation in a cost effective, safe and uninterrupted manner.  In this context, face-to-face meeting hasbeen held with the managers of a company transporting hazardous materialsbetween Gaziantep and Erzurum provinces, and the hazardous materials’transportation routes are selected by SMAA-2 method.
A Stochastic Risk Analysis for the Problem of Route Selection of Hazardous Materials’ Transportation
anemon
Keywords: Tehlikeli Madde Taşımacılığı; Güzergâh Seçimi; SMAA-2; Hazardous Materials; Hazardous Materials Transportation; Route Selection; SMAA-2